Different Phenotypes in Pseudodominant Inherited Retinal Dystrophies - Habibi, Imen; Falfoul, Yosra; Tran, Hoai Viet; El Matri, Khaled; Chebil, Ahmed; El Matri, Leila; Schorderet, Daniel F. (Frontiers in Cell and Developmental Biology, 2021)
Retinal dystrophies (RD) are a group of Mendelian disorders caused by rare genetic variations leading to blindness. A pathogenic variant may manifest in both dominant or recessive mode and clinical and genetic heterogeneity makes it difficult to establish a precise diagnosis. In this study, families with autosomal dominant RD in successive generations were identified, and we aimed to determine the disease’s molecular origin in these consanguineous families. Whole exome sequencing was performed in the index patient of each family. The aim was to determine whether these cases truly represented examples of dominantly inherited RD, or whether another mode of inheritance might be applicable. Six potentially pathogenic variants in 4 genes were identified in 4 families. In index patient with enhanced S-cone syndrome in F1, we identified a new digenetic combination: a heterozygous variant p.[G51A];[=] in RHO and a homozygous pathogenic variant p.[R311Q];[R311Q] in NR2E3. Helicoid subretinal fibrosis associated with recessive NR2E3 variant p.[R311Q];[R311Q] was identified in F2. A new frameshift variant c.[105delG];[105delG] in RDH12 was found in F3 with cone-rod dystrophy. In F4, the compound heterozygous variants p.[R964*];[W758*] were observed in IMPG2 with a retinitis pigmentosa (RP) phenotype. We showed that both affected parents and the offspring, were homozygous for the same variants in all 4 families. Our results provide evidence that in consanguineous families, autosomal recessive can be transmitted as pseudodominant inheritance in RD patients, and further extend our knowledge of pathogenic variants in RD genes.